PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN MERUMUSKAN SOLUSI INOVATIF ISU SDA LOKAL PADA SISWA SEKOLAH DASAR - Sri Wahyuni; Erni Suharini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the necessity to enhance students' skills in problem-solving and formulating innovative solutions for local natural resource (SDA) issues, which are fundamental to environmental citizenship. Initial observations indicated that while students possess basic knowledge of SDA (air, soil, plants, animals), their understanding and application of sustainable management, analysis of exploitation impacts, and proposal of creative solutions were still diverse and needed improvement. This research aims to investigate the influence of the Project-Based Learning (PjBL) model on the ability of fifth-grade students to formulate creative and innovative solutions for local SDA problems. The study employed a Quasi-Experimental design with a sample of fifth-grade students from SD Negeri Gayamsari 02. The PjBL model was implemented through a project titled "Local SDA: Between Benefits and Our Responsibility," where students identified local SDA problems and designed creative action plans. The primary instrument used was a Performance Assessment Rubric focusing on Creativity (DPL 4) and Citizenship (DPL 2) through the presentation of action plans and product creation (posters/infographics). The results showed a significant improvement in the experimental group's ability to formulate innovative solutions (DPL 4) and demonstrate responsible citizenship (DPL 2). Specifically, the average score for the "Creativity and Originality" aspect increased by 25% compared to the baseline group. The PjBL model effectively provided a meaningful and collaborative learning experience, enabling students to connect conceptual knowledge with procedural skills in analyzing problems and creating practical, original solutions for sustainable SDA management. The study concludes that the Project-Based Learning model significantly influences the skill of formulating innovative solutions for local SDA issues in elementary school students.